Debonding failure analysis of prestressed FRP strengthened RC beams - Hoque, Nusrat; Jumaat, Mohd Zamin (Structural Engineering and Mechanics, 2018)
Fiber Reinforced Polymer (FRP), which has a high strength to weight ratio, are now regularly used for strengthening of deficient reinforced concrete (RC) structures. While various researches have been conducted on FRP strengthening, an area that still requires attention is predicting the debonding failure load of prestressed FRP strengthened RC beams. Application of prestressing increases the capacity and reduces the premature failure of the beams largely, though not entirely. Few analytical methods are available to predict the failure loads under flexure failure. With this paucity, this research proposes a method for predicting debonding failure induced by intermediate crack (IC) for prestressed FRP-strengthened beams. The method consists of a numerical study on beams retrofitted with prestressed FRP in the tension side of the beam. The method applies modified Branson moment-curvature analysis together with the global energy balance approach in combination with fracture mechanics criteria to predict failure load for complicated IC-induced failure. The numerically simulated results were compared with published experimental data and the average of theoretical to experimental debonding failure load is found to be 0.93 with a standard deviation of 0.09.